Speeches of Chief Ministers/Lt. Governors at 49th Meeting of the National Development Council at New Delhi on 1st September, 2001 - National Development Council, Planning Commission (National Development Council, Planning Commission, Government of India, 2001)
The 49th Meeting of the National Development Council held in New Delhi on September 1, 2001, served as a crucial forum for deliberations on the Tenth Five-Year Plan, emphasizing the need to harmonize national planning priorities with region-specific developmental realities. Leaders from diverse states and Union Territories—including the Andaman and Nicobar Islands, Chandigarh, Goa, Kerala, Mizoram, Orissa, and Tamil Nadu—highlighted issues such as infrastructure deficits, financial constraints, administrative bottlenecks, and socio-economic disparities. Central themes included the demand for greater financial and operational autonomy, flexible adaptation of Centrally Sponsored Schemes to local conditions, and enhanced investment in transportation, power, tourism, education, and healthcare. Particular attention was drawn to poverty alleviation funding inequities, especially in states like Orissa, where revised allocation methodologies reduced shares despite high poverty ratios, prompting calls for fairer formulas based on both the number and severity of people below the poverty line and the introduction of performance-based incentives. The discussions also underscored the strengthening of Panchayati Raj Institutions through transparency measures, revenue-generating powers, and reinforced Gram Sabha participation to promote accountability and grassroots empowerment. Concerns regarding fiscal burdens arising from Centrally Sponsored Schemes, the need for zero-based budgeting, and demands for Special Category Status for disadvantaged states reflected broader governance and equity challenges. Collectively, the meeting underscored a commitment to decentralized planning, inclusive growth, and cooperative federalism, advocating a development paradigm that integrates economic reforms, social justice, administrative efficiency, and participatory governance to ensure balanced and sustainable progress across India.
Andaman & Nicobar Islands, Chandigarh, Goa, Kerala, Mizoram, Orissa, Tamil Nadu
Keywords: National Development Council; Tenth Five-Year Plan; Regional Disparities; Financial Autonomy; Centrally Sponsored Schemes; Panchayati Raj Institutions; Poverty Alleviation Funding; Special Category Status; Infrastructure Development; Decentralized Planning; Transparency and Accountability; Performance-Based Allocation